Research in regional networks of innovators: a comparative study of four East-German regions - Holger Graf; Tobias Henning (Technische Universität Bergakademie Freiberg, Fakultät für Wirtschaftswissenschaften, 2006)
Universities and public research organisations play a vital role not only in the generation of new technological knowledge, but also in its diffusion. We analyse four East German local networks of innovators which differ in structure and innovative performance and investigate the characteristic role of public research within these local systems of innovation by applying methods of social network analysis on patent data. Our results show that public research organisations are key actors in all regional networks of innovators both in terms of patent output and in terms of centrality of their position in the networks. Further we find the 'thicker' networks to have more central public research organisations.
Keywords: O31; Z13; R11; 330; Innovator networks; public research; R&D cooperation; mobility